Inbred and hybrid sweet corn genotype performance in diverse organic environments. Issue 4 (19th June 2021) - Zystro, Jared; Peters, Tessa E.; Miller, Kathleen M.; Tracy, William F.
Abstract: The value of selection in conventional breeding trials of cultivars destined for organic systems depends on the correlation between systems and relative heritability of key traits. Genotype × environment interaction is a common phenomenon in plant breeding trials. Thus, multiple‐environment testing to identify stable genotypes is a high priority for organic systems. In addition, because organic systems have limited inputs to buffer the environment, they may have greater spatial heterogeneity, which may be better accounted for by additional spatial blocking terms beyond traditional randomized complete‐block design. Over 2 yr, we evaluated 100 hybrid and 40 inbred sweet corn ( Zea mays L.) genotypes in 11 trials in organic systems across six locations and evaluated the addition of augmented incomplete block and row–column design to estimate the performance of sweet corn genotypes. Hybrids differed in their performance for all tested traits. Inbred parents differed in per se performance and general combining ability for all traits. For the hybrid entries, modeling spatial factors beyond the replicated complete blocks improved the model fit for days to anthesis, plant height, ear height, husk protection, ear width, and ear length. For inbred entries, modeling spatial factors beyond the replicated complete blocks improved ∖ model fit for plant height, ear height, tenderness, and ear width. Wricke's ecovalence ( W 2 i ) was a useful measure of stability, correlating reasonably well with two of the three stability statistics considered in this analysis. Based on Wricke's ecovalence, some inbred parents were more stable than others across tested environments in their combining ability for all traits. Core Ideas: We measured stability of sweet corn genotypes and traits over a range of organic environments Determined effectiveness of incomplete blocks designs and spatial adjustment in reducing error For inbreds and hybrid modeling spatial factors beyond RCBs improve fit for most traits Wricke's ecovalence ( W 2 i ) was a useful measure of stability.